Influence of the bitumen properties on the functional and rheological behaviour of asphalt rubber binders - Peralta, J. (2009)
It is estimated that about ten kilograms of tires are discarded per inhabitant annually. The negative impact of this residue can be reduced since rubber can be reused as a constituent of asphalt rubber (AR) builder in road pavements. However, the materials which constitute the AR binders and their interaction are not sufficiently characterized, In this work several base bitumens interacted with crumb rubber in order to produce AR binders, which were subsequently separated, by using a modified Basket drainage method lo recover the residual bitumen and rubber. Additionally, a new “Sphere AR production simulator” method was developed to reproduce the bitumen aging without the contribution of the rubber. EN 12591 and EN 14023 standard tests and the Dynamic Shear Rheometer (DSR) were used lo evaluate the changes in the properties of the binders during AR production. It was observed that the characteristics of the base bitumen significantly affect the AR binder properties (mainly for interactions with softer bitumens).